Non-uniform dust distribution effect on photovoltaic panel performance - Saman S. Jaafar; Hiwa A. Maarof; Renas T. Salh; Hoshang Sahib; Yousif H. Azeez (Renewable Energy and Sustainable Development)
A novel experimental method for power efficiency loss is presented in this paper. It is used to quantitatively determine the impact of dust deposition on the PV power generation panel. To determine the selection range of unknown parameters in the experiment process, a photovoltaic panel with five collected dust samples (Toner (C), Soil, Cement (CaO, SiO4), Gypsum (Ca2SO4.2H2O), and Sand (AL2O3, SiO4)) is designed. According to experimental results, the extinction coefficient for the five pollutants are recorded. Eventually, the impact of dusts on the results is proofed by repeating in two continuous days of same conditions. The results show that the proposed process has a high effect on the reduction of output power (62% to 96%), decrease of irradiance (34% to 93%) and increase of output power due to increase of tilt angle as a doubling of power except toner.  The experimental and calculated results are in agreement. The results show that non-uniform distribution of dust deposit pollutants on the photovoltaic panel significantly reduces the power output. Received: 09 January 2023 Accepted: 06 February 2023 Published: 16 February 2023